Cochrane at crossroads over drug company sponsorship - Moynihan, Ray (BMJ Publishing Group Ltd., 2003)
Can independent scientific evaluation be sponsored by vested interests? The Cochrane Collaboration's decision on this question at its annual colloquium next week could have a big effect on its future